Application of bulk nanobubbles in ultrafiltration and spray drying of dairy concentrates - Sajith Babu, Karthik (Kansas State University, 2022)
Milk protein concentrates (MPC) are ideal dairy ingredient to provide nutritional and functional benefits in high-protein dairy and food products. However, one of the key challenges encountered by the MPC manufacturers during the spray drying is the high viscosity after ultrafiltration and evaporation. Reducing viscosity and aiding an increase in the solid levels before spray drying can offer significant savings on the overall energy cost during spray drying. On the other side, it is also a challenge for the end-user to incorporate the MPC powders in a formulation due to their poor rehydration properties. Therefore, simple and innovative strategies to reduce viscosity before spray drying while also improving final powder properties are of critical consideration for the dairy industry. Moreover, the dairy industry's eco-efficiency strategy focuses on manufacturing high-quality dairy products at a low cost with minimal environmental impact are gaining more attention. For instance, reduced energy usage while keeping high permeation flux values is critical for eco-efficiency. In this research, application of bulk nanobubbles (NBs) for improving the processability and functionality of various dairy concentrates were evaluated. The chapter 3, 4, and 5 investigated the use of NBs generated by hydrodynamic and acoustic cavitation for improving the processability of dairy concentrates, rehydration/flow properties of MPCs. Control and NB-MPC dispersions were evaluated in terms of rheological behavior and microstructure. Additionally, MPC dispersions were spray dried after the NB treatment and the resultant NB-MPC powders were characterized and compared with the control MPCs in terms of rehydration characteristics and microstructure. NB-MPC powders exhibited better rehydration properties than the control MPC powders. Overall, these studies therefore, recommends the possibility of using NB treatment for more efficient drying while improving the functional properties of the resultant MPC powders. The chapter 6 evaluated the influence of NB incorporation during the UF process of skim milk. Both lab and pilot-scale UF experiments were conducted to evaluate the effect of NB incorporation on UF process by evaluating permeate flux, membrane microstructure, fouling resistance, energy consumption, and skim milk concentrate characteristics. For both the lab/pilot-scale runs, after the initial water flux measurements, the membrane was fouled with the skim milk concentrate dispersions operated at 20°C under a constant transmembrane pressure 30 psi in constant concentration mode (the permeate was returned to the feed tank at regular 10-min intervals) and the total run time was fixed for 1 hour. The results revealed that NB treatment had a significant effect on permeate flux in both the lab and pilot-scale runs. Overall, the NB treatment helped to improve UF membrane performance and therefore this study suggests the potential of using NB treatment for a more efficient UF processing.
Keywords: Bulk nanobubbles; Ultrafiltration; Milk protein concentrate; Rehydration; Spray drying; Sustainability